Determination of Vertical Boundaries of National Airspace in the Context of Airspace Security Operations - Rohanwi, Fatkur; Buaton, Tiarsen; Makbul, Ahmad (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The establishment of the vertical boundary of national airspace is crucial in maintaining Indonesia's air sovereignty. The state has full sovereignty over the airspace above its land and waters; however, to date, there are no clear national or international regulations that define this vertical boundary. This uncertainty creates issues in law enforcement operations and airspace security, especially due to the rapid advancement of aviation and space technologies. This study analyzes the importance of establishing the vertical boundary of airspace to support air security operations by the Indonesian Air Force (TNI AU). The research employs a qualitative approach through literature reviews and interviews with relevant experts. The findings indicate that setting the vertical boundary is urgent in ensuring air security and sovereignty, as well as in preventing future legal conflicts. Active diplomacy in international forums is necessary to foster global agreements on the vertical boundary of airspace.